Niveles de harina de cáscara de maracuyá (Passiflora edulis) en elaboración de yogur natural. finca experimental la María, Mocache-Ecuador 2013 Quevedo. - Quintero Mora, Karla Rocío (2013)
In Dairy Plant, Faculty of Animal Science. This research was conducted at the Experimental Farm "La María" of Quevedo State Technical University, Laboratory of Food Science, Faculty of Animal Science, located at Km 71 /2 pathway Quevedo - El Empalme, in Los Rios province, adding three levels of flour rind passion fruit (0.5, 1.0, and 1.5 % ) was in the manufacture of yoghurt, compared with control treatment ( 0 % of passion fruit peel flour ) distributed under a completely randomized design, with five replicates per treatment and is experimental unit two liters of milk. The inclusion of fiber passion fruit peel meal (HCM ) in yogurt , no statistically affected the physicochemical properties, however present total solids content of 15.34 to 18.48 and a significant protein content of 2.31 to 3.08 %, the same as if affected statistically , the organoleptic assessment was influenced by the addition of different levels of HCM, showing the changes in the intensity of the characteristics evaluated by the panel of tasters, with the yogurt with 2.0 % of HCM which I present a suitable sensory profile and acceptance thereof. Through the absence of microbiological analysis of E.coli, so Staphilococcos can show a proper hygiene and handling are determined. The use of HCM in the development of natural yoghurt was determined that there is an increase in costs as the levels of this additive increase, compared to the control treatment using an input that allows improve the physical, chemical properties and organoleptic qualities in providing functional yogurt is an intangible economic indicator.